Determinants of Decision to Revisit Among Millennial Muslim Tourist in Halal Tourism Destination: Evidence from Bukittinggi City - Mardhiyah, Rahadatul; Saleh, Samsubar; Donna, Duddy Roesmara (Likuid Jurnal Ekonomi Industri Halal, 2025)
This study aims to analyze the factors that influence the decision to revisit millennial Muslims to the halal tourist area of Bukittinggi City. This research uses the Theory of Planned Behavior as a basis. This research uses quantitative methods and is analyzed using Structural Equation Modeling - Least Square Partial (SEM-PLS) mode. The sampling method in this study ussed nonprobability sampling with purposive sampling technique. Respondents used were 218 tourists who returned to the halal tourism area of Bukittinggi City. The results showed that destination image and service quality had a significant effect on revisit decisions. Meanwhile, halal awareness does not significantly influence the decision to revisit millennial Muslims to the halal tourist area of Bukittinggi City. From the research results, two things need to be improved, namely the destination image and quality of service towards the decision to revisit Millennial Muslim